A study of some growth parameters for common carp Carpinus carpio L cultured in floating cages. - Jasim, Ruaa Mohammed; Kamil Kadhim Fahad (University of Thi-Qar Journal of agricultural research, 2023)
The current study included measuring some of the chemical and physical properties of the water of the study area and estimating the concentration of three heavy elements (lead, copper, zinc) in the tissues of common carp Cyprinus carpio L (gills, muscles, viscera) and measuring growth rates and weight gains at three different densities. The samples were collected from a private farm that raises fish in floating cages on the Euphrates River from 11/18/2022 to 4/18/2023 Different densities were also studied to obtain the best culture density. Three densities (21_25_28 fish / m3) were used, with 500 fish for the first treatment, 900 fish for the second treatment, and 1100 fish for the third treatment, with an average weight of (120_140) g. Diet of Iranian origin was used for the three treatments. The results of the statistical analysis showed that there were significant differences during the months of the study, where the highest rate was in the month of March. And between the qualitative growth rate and the presence of significant differences between the months of the study, where the highest rate was in the month of February. The rate of feed conversion and the efficiency of feed conversion when conducting the statistical analysis indicated that there were significant differences, as the highest rate was in the month of November, as well as between the chemical analysis of fish muscles at the beginning of the experiment and the end of the experiment.